Adolescent Sexual and Reproductive Health in Burkina Faso - Cortez, Rafael (World Bank, Washington, DC, 2015)
Today s adolescents and youth face substantial physical, social, legal, and economic barriers to meeting their SRH potential. Key factors underlying these issues are a lack of adolescent SRH (ASRH) policies and access to accessible, affordable, and appropriate health services. The impact that these factors have on adolescent health and development is clearly seen in Burkina Faso. Burkinabè adolescent girls face high adolescent fertility rates, early and forced marriage, an increased risk of maternal mortality, and a high unmet need for contraception, among others. Adding to this issue is a lack of access to education, basic health information, and SRH services, contributing to a lack of awareness and knowledge about SRH and traditional and harmful gender stereotypes. The objectives of the study were to understand the impact that structural and proximal determinants have on access to ASRH services and health outcomes; and the impact that recently implemented policies and programs have on ASRH.